Computer vision and image processing fundamentals and applications - Bhuyan, Manas Kamal (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
The book familiarizes readers with fundamental concepts and issues related to computer vision and major approaches that address them. The focus of the book is on image acquisition and image formation models, radiometric models of image formation, image formation in the camera, image processing concepts, concept of feature extraction and feature selection for pattern classification/recognition, and advanced concepts like object classification, object tracking, image-based rendering, and image registration. Intended to be a companion to a typical teaching course on computer vision, the book takes a problem-solving approach.
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Computer Graphics / General; COMPUTERS / Machine Theory; TECHNOLOGY / Electricity; Computer vision; Image processing